Implementation of Business Intelligence for Analyzing and Visualizing Data on Hacker-Affected Regions Using Data Studio - Fitrianik Eva Lestari; Budi Yanto (JOURNAL OF ICT APLICATIONS AND SYSTEM, 2024)
Implementation of Business Intelligence (BI) using the Google Data Studio platform facilitates the analysis and visualization of data from regions impacted by hacking activities. This study demonstrates the use of a data warehouse to integrate multiple datasets, enabling the generation of accurate, interactive dashboards for informed decision-making. Results highlight the effectiveness of BI in transforming raw data into meaningful insights through visual elements such as bar charts, pie charts, and scatter plots. The analysis provides actionable insights into areas affected by cyberattacks, emphasizing the importance of accessible and real-time data visualization tools. Findings validate the role of Google Data Studio in enhancing organizational responsiveness to security threats through intuitive and customizable reporting solutions.